Improvement of hotel “Las Cuevas” warehouse logistics - González Cabrera, Ernesto; Cespón Castro, Roberto; Coello Machado, Norge Isaías; Glistau, Elke (My University, 2022)
This research is carried out in the hotel "Las Cuevas", located less than 400 meters from the historic centre of the municipality of Trinidad, Sancti Spíritus, with the objective of applying a procedure that allows the analysis and improvement of the logistics of warehouses in the hotel. For this purpose, information collection and analysis techniques are used, such as: bibliographic review, document review, consultation with specialists, direct observation, interviews, application of a checklist, among others, which make possible the veracity and accuracy of the results of the study. Logistics in general plays an important role in the world and national panorama at present, since it has been established in recent years as a new way of approaching business management, having become a competitive tool within the development strategies of companies. The application of the selected procedure, which includes a general characterization of the hotel, a general characterization of the warehouse under study and a diagnosis of its current situation, concludes with an analysis of the problems detected and improvement proposals to achieve the improvement of logistics in the beverage and liquor warehouse so that it can be certified at the current level or higher.
Keywords: Warehouse Logistics; Certification; Checklist; Supply Chain; Logística de Almacén; Cadena de Suministro